TDAH e comportamento infantil: análise de um (des) curso entre o dito e o não dito - Reisdorfer, Caroline Maria Braciak (2017)
This dissertation works, using as method the French Discourse Analysis, discursive elements that produce effects of meaning aboutthe idea of childhood. The central theoretical question is the relationship between said and unsaid, taking silence as an important ingredient for the articulation of the senses that the discourse presents about the theme of the corpus will be analysed.This study was built using texts of Pêcheux (year), Lacan (year), Althusser (year) and Orlandi (year), allowing to print the theory over the chosen corpus, which groups the 18 criteria used by doctors, psi area professionals, teachers and parents in order to observe the behavior of children who present conflicting behaviors in relation to activities in the school, family and social space. These criteria, when they occur in 6-month recurrence and in groups of 6 symptoms, lead professionals to conclude that the child has Attention Deficit / Hyperactivity Disorder. The materiality of the discursive sequences circulates in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders published by the American Psychiatric Association and occupies the status that is ideologically attributed to Medicine because it is considered as a science of care and many specific treatment solutions, whether using medicinal treatment or not. Thus, this research aims to devote a look at extra linguistic and therefore discursive relationships, in order to understand what the manual states about child behavior. It was necessary, in this sense, to consider the conditions of production of the discursive sequences and also the sequences themselves, that is, for the criteria, and to understand the discourse as a theoretical object, to understand how the course on childhood is diverted to another look and another speech about it. For this, this work used the studies of Postman (year), Del Priori (year) and Ariès (year), as well as laws and data from government agencies, both on the child and on the disorder that is represented by the discourse of the manual. It is believed that the material studied in this work represents a pertinent articulation to think about the profile of the child desired inthe present time, understanding that this objective can be reached through the discursive effects of meaning of the manual on a supposed "pathology". It is in the midst of what is said about the abnormality and the unsaid about normality that it is possible to obtain defenses of theses anchored on previous discourses, either in the sense of ratifying them or of rejecting them by means of silencing.